2017
DOI: 10.1080/00140139.2017.1303085
|View full text |Cite
|
Sign up to set email alerts
|

Job design, employment practices and well-being: a systematic review of intervention studies

Abstract: There is inconsistent evidence that deliberate attempts to improve job design realise improvements in well-being. We investigated the role of other employment practices, either as instruments for job redesign or as instruments that augment job redesign. Our primary outcome was well-being. Where studies also assessed performance, we considered performance as an outcome. We reviewed 33 intervention studies. We found that well-being and performance may be improved by: training workers to improve their own jobs; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 84 publications
3
58
0
2
Order By: Relevance
“…Organisational level interventions (e.g., Nielsen & Abildgaard, ; Nielsen, Taris, & Cox, ) would have been an alternative approach, but given the unique organisational and economic circumstances, they were not feasible. Furthermore, past systematic reviews and meta‐analysis demonstrate that organisational level interventions have mixed results, and that cognitive‐emotional interventions at the individual level showed the strongest effects sizes (Daniels, Gedikli, Watson, Semkina, & Vaughn, ; Richardson & Rothstein, ). Our research demonstrated that individual level interventions can be effective under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Organisational level interventions (e.g., Nielsen & Abildgaard, ; Nielsen, Taris, & Cox, ) would have been an alternative approach, but given the unique organisational and economic circumstances, they were not feasible. Furthermore, past systematic reviews and meta‐analysis demonstrate that organisational level interventions have mixed results, and that cognitive‐emotional interventions at the individual level showed the strongest effects sizes (Daniels, Gedikli, Watson, Semkina, & Vaughn, ; Richardson & Rothstein, ). Our research demonstrated that individual level interventions can be effective under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Such initiatives are important to create engaging work environments and ensure that current employees are all able to create the circumstances that allow them to thrive at work. Employee involvement in such interventions is key, as previous studies have shown that individual level crafting interventions appear to be more successful than collective, participatory job redesign interventions (Daniels, Gedikli, Watson, Semkina, & Vaughn, 2017).…”
Section: Studymentioning
confidence: 99%
“…There is also considerable evidence for interaction effects where job resources buffer the adverse effects of job demands on strain and the combination of job resources and job demands boosts work engagement (e.g., Bakker, Hakanen, Demerouti, & Xanthopoulou, , ; Hakanen, Bakker, & Demerouti, ). In addition, longitudinal and intervention studies show that increasing job resources can lead to these desirable outcomes (e.g., Daniels, Gedikli, Watson, Semkina, & Vaughn, ; Holman & Axtell, ; Van Wingerden, Bakker, & Derks, ).…”
Section: Introductionmentioning
confidence: 99%